Analysis and Prediction of Subway Settlement Deformation Based on Grey Model. Issue 1 (February 2021) - Shufen, Zheng; Jing, Wen
Abstract: In this paper, the monitoring data of settlement and deformation along the western section of a metro in H city are collated and analyzed, the actual situation of settlement and deformation is grasped, and the long-term settlement and deformation trend are predicted by using grey prediction model. In the process of forecasting, a non-equidistant grey forecasting model is established by using the data of the first several groups of monitoring points, and the predicted values are compared with the last group of monitoring data to verify the reliability of the model and further optimize the model. Then, the optimized model is used to predict the long-term settlement deformation of the subway, which provides a basis for the deformation control and management of the subway.